Transcriptomic Signatures Associated With Gray Matter Volume Changes in Patients With Functional Constipation - Cai, Wangli; Zhou, Yujing; Wan, Lidi; Zhang, Ruiling; Hua, Ting; Gong, Jian; Yang, Bo; Tang, Guangyu (Frontiers in Neuroscience, 2022)
Functional constipation, which belongs to the functional gastrointestinal disorder (FGID), is a common disease and significantly impacts daily life. FGID patients have been progressively proven with functional and structural alterations in various brain regions, but whether and how functional constipation affects the brain gray matter volume (GMV) remains unclear; besides which genes are associated with the GMV changes in functional constipation is largely unknown. On account of the structural MRI image from the 30 functional constipation patients and 30 healthy controls (HC), GMV analysis showed that functional constipation patients had significantly decreased GMV in the right orbital prefrontal cortex (OFC), left precentral gyrus (PreG) and bilateral thalamus (THA). Correlation analysis showed that the self-rating depressive scale, patient assessment of constipation quality of life (PAC-QOL) and Wexner constipation scores were negatively correlated with GMV of the OFC, and negative correlations between PAC-QOL score and GMV of the bilateral THA. Based on the Allen Human Brain Atlas, a cross-sample spatial correlation was conducted and found 18 genes’ expression values showed robust correlations with GMV changes in Functional constipation patients. These outcomes highlight our recognition of the transcriptional features related to GMV changes in functional constipation and could be regarded as candidates to detect biological mechanisms of abnormality in functional constipation patients.